ChemInform Abstract: Gold(I)‐Catalyzed Highly Stereoselective Synthesis of Polycyclic Indolines: The Construction of Four Contiguous Stereocenters. Issue 18 (April 2016) - Yang, Jin‐Ming; Li, Peng‐Hua; Wei, Yin; Tang, Xiang‐Ying; Shi, Min
Abstract: The selective formation of either the oxa‐bridged‐ring system (III) or ring‐opened polycyclic indoline derivatives (II) is controlled by using different gold‐catalyst systems.